2001
DOI: 10.1063/1.1418023
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of cobalt layers in Co/Cu multilayers monitored by magnetic and magnetoresistive measurements

Abstract: We have monitored the structural evolution of Co(tCo)/Cu(4xtCo) multilayers when tCo ranges from 12 to 2 Å. The investigation has been performed by studying their magnetization and giant magnetoresistance, since these properties are complementary in providing information about the structure of the magnetic species into the samples. In particular, in the intermediate range of thickness, we observed no correspondence between magnetic and magnetoresistive behavior. Finally, at sufficiently low thickness, the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
5
19
0
1
Order By: Relevance
“…The typical SPM moments obtained previously on electrodeposited Co/Cu multilayers [32][33][34][35][36] Previous reports by other researchers on both electrodeposited [36,37] and sputtered [38][39][40] Co/Cu multilayers with very thin Co layers around 1 nm and below gave further support to our findings and conclusions concerning the appearance of SPM regions in such multilayers. Namely, it turned out from these studies when increasing the Co layer thickness in the subnanometer range that whereas the M(H) curves evolve from a hysteresis-less behavior to the appearance of a clear hysteresis, i.e., the formation of FM regions, the MR(H) curves remain still strongly non-saturating with negligible hysteresis.…”
Section: Co/cu Multilayerssupporting
confidence: 91%
See 2 more Smart Citations
“…The typical SPM moments obtained previously on electrodeposited Co/Cu multilayers [32][33][34][35][36] Previous reports by other researchers on both electrodeposited [36,37] and sputtered [38][39][40] Co/Cu multilayers with very thin Co layers around 1 nm and below gave further support to our findings and conclusions concerning the appearance of SPM regions in such multilayers. Namely, it turned out from these studies when increasing the Co layer thickness in the subnanometer range that whereas the M(H) curves evolve from a hysteresis-less behavior to the appearance of a clear hysteresis, i.e., the formation of FM regions, the MR(H) curves remain still strongly non-saturating with negligible hysteresis.…”
Section: Co/cu Multilayerssupporting
confidence: 91%
“…Namely, it turned out from these studies when increasing the Co layer thickness in the subnanometer range that whereas the M(H) curves evolve from a hysteresis-less behavior to the appearance of a clear hysteresis, i.e., the formation of FM regions, the MR(H) curves remain still strongly non-saturating with negligible hysteresis. Along this line, Spizzo et al [38] concluded that since the M(H) and MR(H) curves evolve differently with Co layer thickness, they should have different origin and have given a very reasonable explanation for this behavior. Namely, in order to understand this difference, one has to consider that the electronic mean free path related to spin flipping is of the order of a few tens of nanometers.…”
Section: Co/cu Multilayersmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing iron content above x ¼ 27 the samples magnetic behaviour changed and M-loops pointed out a transition from superparamagnetic to ferromagnetic-like behaviour. On the contrary, GMR data showed no evidence of this transition, as magnetoresistive loops shape, in the same range of concentration, was almost independent of x: Since magnetisation and GMR measurements sense a magnetic structure with different length scales [2], this effect could be ascribed to the coexistence of various magnetic orderings. For instance, we could have homogeneous magnetic regions with a different magnetic behaviour, e.g.…”
mentioning
confidence: 86%
“…В отличие от слоевых пленок такие " квазигранулированные" (кластерно-слоистые) пленки имеют изотропный эффект ГМС, пренебрежимо малый гистерезис намагниченности и показывают суперпара-магнитное (SPM) поведение. Дальнейшие исследования магнитных и магнитотранспортных свойств Co/Cu пока-зали, что толщина слоев Co, способы и условия напыле-ния образцов существенно влияют на формирование и свойства " квазигранулированных" пленок [11][12][13][14][15]. Объектами исследования в настоящей работе явля-ются мультислойные наноструктуры Co(t x , ¦ )/Cu(9.6 ¦ ) (0.3 ¦ ≤ t Co ≤ 15 ¦ ), обладающие гигантским магнито-сопротивлением.…”
Section: Introductionunclassified